Pengaruh Pemanasan Terhadap Kristalinitas Dan Parameter Kisi Nanokomposit Silika-Zirkonia Montmorillonit K10 Dan Silika-Besi Oksida Montmorillonit K10 - Sekewael, Serly J.; Wijaya, Karna; ., Triyono (Indonesian Journal of Chemical Research, 2018)
The thermal treatment of the silica-zirconia montmorillonite K10 and silica-ferri oxide montmorillonite K10 nanocomposites at 300 and 500 Â°C has been carried out, respectively as part of a study of their function as the catalyst. The heating effect on the crystallinity and the lattice parameter calculation of both nanocomposites was studied using XRD and FTIR instruments. The results showed that the nanocomposite silica-zirconia montmorillonite K10 has a thermal resistance and the crystallinity better than the silica-ferri oxide montmorillonite K10, and both have values varying lattice parameters.